Influence of whole-body vibration and gait training with additional load on functioning, balance, and gait in patients with Parkinson’s disease (Research, Society and Development, 2022)
Parkinson’s disease (PD) is characterized by the selective loss of dopaminergic neurons from the substantia nigra compacta and nigrostriatal pathway, which leads to sensory and motor impairments. The aim of the present study was to compare the effect of whole-body vibration and gait training with additional load on functioning, balance and gait in patients with PD. Twenty-two male and female patients (mean age: 61 ± 5.6 years) were randomly allocated to a Control Group (CG), Vibration Group (VG), or Added Weight Group (AWG). The following evaluations were performed before and after the intervention: Unified Parkinson’s Disease Rating Scale – subscales “Activities of Daily Living” and “Motor Examination”; Tinetti Test, Timed Up and Go test, Berg Balance Scale, and baropodometry. The ordinal variables were evaluated using the Kruskal-Wallis test (p ≤ 0.05) and the numerical variables were analyzed using two-way ANOVA followed by the Student-Newman-Keuls post hoc test (p ≤ 0.05). The results demonstrated a significant increase in functioning, balance, and gait quality in the VG and AWG compared to the CG. Vibration training and gait training with additional weight exert a positive influence on functioning, balance, and gait in patients with PD. Other studies can be carried out comparing the effect of the vibratory training with the partial weight support and the addition of body weight using the same variables of the present research.